Developing criteria and variables for evaluating the effects of vegetation on single-family houses / Alamah Misni - Misni, Alamah (Faculty of Architecture, Planning & Surveying, 2015)
This paper describes the methodology used to measure the effects of surrounding vegetation, building construction and human factors on a small number of individual houses and a large number of single-family houses. The primary data were obtained from fieldwork and site measurements during a two-stage process. All supporting data for this study was sourced from various Malaysian government departments. Fieldwork in the first stage focused on five individual single-family houses. Quantitative measurements were taken to record the construction of the buildings, their surrounding vegetation, human factors, and weather data during the daytime. In this report only five houses of different ages and types of landscaping were chosen to compare the effect of landscaping on the thermal performance of the house. These five houses had used different styles and designs of tropical landscaping, which could produce different conditions of micro-climates. The air temperature, relative humidity and wind speed data were obtained from the exterior and interior of houses during similar weather conditions to ensure they could be accurately compared. This data was automatically recorded at half hour intervals by static and mobile sensors of the data loggers. The albedo data for every type of building were also measured during the day time. In the second stage, the fieldwork measurements were divided into four categories: building construction, landscaping, human factors, and weather data. The annual energy consumption for every house was also evaluated by analysing electricity consumption for different single-family houses ranging in age from 3 to 40 years. The target number of respondents was 50 houses. Statistical calculation and analysis was used to measure and evaluate the energy saving.